2007
DOI: 10.1051/fruits:2007037
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and host plants ofBactrocera cucurbitaein West and Central Africa.

Abstract: Distribution and host plants of Bactrocera cucurbitae in West and Central Africa. Abstract-Introduction. The data on Bactrocera cucurbitae collected over a large area of West Africa for around the past ten years enables us to make a synthesis, since this economically significant species is now widespread. Fruit samples were collected in the course of various trips to Africa; we focused on looking for the melon fly, B. cucurbitae (Coquillett). Equipment and methods. The Tephritidae were captured by means of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
10

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 8 publications
1
41
1
10
Order By: Relevance
“…the two regions with highest species richness are among the Critical ones: east Guinean Forest and Nigerian Lowland Forest. In the last decade two invasive species of Asian origin have been recorded from western Africa: Bactrocera invadens Drew, Tsuruta & White, 2005(Drew et al 2005Goergen et al 2011) and B. cucurbitae Coquillett 1899 (Vayssières et al 2007). Both, particularly the former, are known to show competitive displacement of indigenous species (Ekesi et al 2009, Mwatawala et al 2009, and are now found in all countries and ecoregions of the study area.…”
Section: De Meyer M White Im and Goodger Kfm Frugivorous Fruit mentioning
confidence: 99%
“…the two regions with highest species richness are among the Critical ones: east Guinean Forest and Nigerian Lowland Forest. In the last decade two invasive species of Asian origin have been recorded from western Africa: Bactrocera invadens Drew, Tsuruta & White, 2005(Drew et al 2005Goergen et al 2011) and B. cucurbitae Coquillett 1899 (Vayssières et al 2007). Both, particularly the former, are known to show competitive displacement of indigenous species (Ekesi et al 2009, Mwatawala et al 2009, and are now found in all countries and ecoregions of the study area.…”
Section: De Meyer M White Im and Goodger Kfm Frugivorous Fruit mentioning
confidence: 99%
“…Its current distribution ranges from South Asia, whence it originates, to many Pacific Islands (including Hawaii) and, more recently, the Seychelles and Africa, where it is currently spreading [6]. Its biology is relatively well known, and the species has been much studied in India, South-East Asia and Hawaii [7].…”
Section: Inventory and Distributionmentioning
confidence: 99%
“…In Reunion Island, besides Cucurbitaceae, we can report rare attacks on the tomato, wild passion fruit (Passiflora foetida L.) and passion fruit (Passiflora edulis Sims) [4]. We noted that B. cucurbitae attacks the tomato and papaya little or not at all (Carica papaya L.) in this island, whereas it causes damage to these crops in other parts: India [19], Cameroon [20], Hawaii [21] and Benin [6]. This probably results from competition for resources with N. cyanescens for the tomato, and with various fruit fly species (Ceratitis spp.)…”
Section: Biology and Behaviormentioning
confidence: 99%
“…These two Asian Batrocera invaders remain major horticultural pest species, widespread not just in Senegal, where B. invadens predominates on fruit crops [28] and B. cucurbitae on vegetable crops [31], but also in 14 other West African countries.…”
Section: Major and Minor Pest Speciesmentioning
confidence: 99%
“…The first collection of the melon fly in Senegal was carried out on November 5, 2003 [31] with collections of infested Momordica charantia around Dakar; the preliminary data from which was therefore checked in the following year.…”
Section: Fruit Fly Inventorymentioning
confidence: 99%